Odpowiedzi

2010-02-18T20:52:13+01:00
I.
0.2(x=2) - 0,3(y - 2) = 0,1
0,7(x-1)+0,1(y+5)=0,1

0.2x + 0,4 -0,3y +0,6 =0.1
0,7x - 0.7 +0.1y + 0.5 = 0.1

0,2x= 0.1 - 0.4 + 0.3y -0.6 / :0,2
0.7x - 0,7 + 0,1 y +0.5 = 0.1

x=0,1 - 0.4 + 0.3y - 0,6/ ( to wszystko cały ułamek podzielić przez) 2
0,7(0,1-0,4+0,3y-0,3)-0,7+0,1y+0,5=0,1
0,7 - 0,28 +0,21y-0,21-0,7+0,1y+0,5=0.1
0,21y + 0,1y= 0,1-0,07+0,28+0,21+0,7-0,5+0,31y=7,2/:0,31
Y~~23
0,2x=0.1-0.4+0.3(23)-0,3+0,2x=6,3/:0.2+x=35

II.
0,6(x+2)-0,7(y-2)=-0,1
0,4(x-2)+0,3(y+2)=0,3
0.6x+0,12-0.7y+0,14=-0,1
0,4x-0,8+0,3y+0,6=0,3
0,6x=-0,1-0,12+0,7y-0,14/:6
0,4x-0,8+0,3y+0,6=0,3
x=-0,1-02(tutaj skrócasz z 6 i -0.12) +0,7y -0,14
0,4(-0,1-02 +0,7y -0,14)-0,8+0,3y+0,6=0,3
x=-0,1-02 +0,7y -0,14
-0,04 -0,08 + 0.28y - 0,56 -0,8 + 0,3y +0,6 =0.3
x=-0,1-02 +0,7y -0,14
0.28y +0.3y =0.3+0,04+0,08 +0,56 +0,8 -0,6
x=-0,1-02 +0,7y -0,14
0.58y=1.8/0.56
y~~2
x=-0,1-02 +0,7(2) -0,14
x=0.96

1 1 1